Gringo injustice : insider perspectives on police, gangs, and law - Mirandé, Alfredo (Routledge, Taylor & Francis Group, 2020)
"The recent mass shooting of 22 innocent people in El Paso by a lone White gunman looking to "kill Mexicans" is not new. It is part of a long, bloody history of anti-Latina/o violence in the United States. Gringo Injustice brings this history to life, shedding critical light on the complex relationship between Latinas/os and the United States' legal and judicial system. Contributors with first-hand knowledge and experience, including former law enforcement officers, ex-gang members, attorneys, and community activists, share insider perspectives on the issues facing Latinas/os and initiate a critical dialogue on this neglected topic. Essays examine the unauthorized use of deadly force by police and patterned incidents of lynching, hate crimes, gang violence, and racial profiling. The book also highlights the hyper-criminalization of barrio youth and considers wide-ranging implications from the disproportionate imprisonment of Latinas/os. Gringo Injustice provides a comprehensive and powerful look into the Latina/o community's fraught history with law enforcement and the American judicial system. It is an essential reference for students and scholars interested in intersections between crime and communities of Color."--Page iii